2021
DOI: 10.1186/s12991-021-00354-2
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde concentrations in obsessive–compulsive disorder: a systematic review and meta-analysis

Abstract: Background This meta-analysis aimed to investigate serum and plasma malondialdehyde (MDA) levels in patients with obsessive–compulsive disorder (OCD) in comparison to healthy controls. Methods Following the PRISMA protocol, we searched for the relevant studies through the databases of Scopus, PubMed, Google Scholar, and web of science until September 2019 with no time restriction. Overall, nine studies were included in the current meta-analysis. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Also, patients with OCD had lower ATPase activity compared to healthy controls. Some case control studies [36][37][38][39][40][41][42][43] and a metaanalysis [44] concentrated on the relationship between OCD and MDA. In contrast with our study, Ranjekar et al [45] observed no significant differences in serum levels of lipid peroxidation markers between patients with schizophrenic and healthy control, and R. Kurup and P. Kurup [46] found that OCD patients had lower MDA level than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Also, patients with OCD had lower ATPase activity compared to healthy controls. Some case control studies [36][37][38][39][40][41][42][43] and a metaanalysis [44] concentrated on the relationship between OCD and MDA. In contrast with our study, Ranjekar et al [45] observed no significant differences in serum levels of lipid peroxidation markers between patients with schizophrenic and healthy control, and R. Kurup and P. Kurup [46] found that OCD patients had lower MDA level than controls.…”
Section: Discussionmentioning
confidence: 99%
“…Increased MDA concentrations in peripheral blood samples has been proposed as a biochemical biomarker for the diagnosis and evaluation of the severity of the symptoms of OCD in several independent studies ( 48 - 52 ). A recent meta-analysis indicated that serum/plasma concentrations of MDA are positively correlated OCD pathology in human subjects ( 53 ). Such systemic redox imbalances have also been proposed by another independent meta-analytical study, wherein the authors reported significant positive association of oxidative damage markers such as 8-hydroxydeoxyguanosine (8-OHdG) and MDA, in addition to a negative correlation of endogenous antioxidant systems ( e.g.…”
Section: Malondialdehydementioning
confidence: 99%